Assessment of children presenting with history of pica for iron deficiency anaemia by serum ferritin estimation - Najeeb, Shahzad; Shah, Sajid Hussain; Aalia, Bibi; Sarwar, Shabana; Khan, Asfandyar; Hussain, Ejaz (Pakistan Journal of Physiology, 2020)
Background: Pica is persistent ingestion of non-nutritive substances for at least one month mostly after the age of 2 years. Pica is common presentation of iron deficiency anaemia. This study aimed to assess children for iron deficiency anaemia presenting with history of pica by serum ferritin estimation. Methods: This study was done over one year in Ayub Teaching Hospital, Abbottabad. Children of either sex above two years presenting with history of pica were included. Patient history of pica substance and nutrition along with milk intake, age, sex, weight, height, was documented on proforma. Data was analysed on SPSS-20 and results were taken significant with p<0.05. Results: A total of 120 patients, 59 (49.2%) males and 61 (50.8%) females, were recruited. Their age range was 2–10 years; weight ranged 6.8–40 Kg with mean weight 12.55±3.43 Kg. Height ranged from 70.5 to 154 Cm with mean height 90.5±10.48 Cm. Haemoglobin ranged from 5.3 to 11.9 gm/dl with mean Hb 8.81±1.21 gm/dl. Mean serum ferritin level was 7.3±4.28 ?g/ml. Substances eaten were soil, sand and lime accounting for 72.5%. Twenty percent children were breast fed. There was significant relationship between weight and height with pica (p<0.001). Conclusion: Pica is one of the common presentations of iron deficiency anaemia and most of the parents ignore this as if this is not manifestation of disease, rather consider it to be habit of child. Any child presenting with pica history should be evaluated for iron deficiency anaemia. Pak J Physiol 2020;16(2):48?51